Calorimetry of dehydrogenation and dangling-bond recombination in several hydrogenated amorphous silicon materials - Roura, P.; Farjas, J.; Rath, C.; Serra-Miralles, J.; Bertran, E.; Roca I Cabarrocas, P. (My University, 2006)
Differential scanning calorimetry (DSC) was used to study the dehydrogenation processes that take place in three hydrogenated amorphous silicon materials: nanoparticles, polymorphous silicon, and conventional device-quality amorphous silicon. Comparison of DSC thermograms with evolved gas analysis (EGA) has led to the identification of four dehydrogenation processes arising from polymeric chains (A), SiH groups at the surfaces of internal voids (A′), SiH groups at interfaces (B), and in the bulk (C). All of them are slightly exothermic with enthalpies below 50 meV (H atoms), indicating that, after dissociation of any SiH group, most dangling bonds recombine. The kinetics of the three low-temperature processes [with DSC peak temperatures at around 320 (A), 360 (A′), and 430°C (B)] exhibit a kinetic-compensation effect characterized by a linear relationship between the activation entropy and enthalpy, which constitutes their signature. Their Si H bond-dissociation energies have been determined to be E (Si H)0 =3.14 (A), 3.19 (A′), and 3.28 eV (B). In these cases it was possible to extract the formation energy E (DB) of the dangling bonds that recombine after Si H bond breaking [0.97 (A), 1.05 (A′), and 1.12 (B)]. It is concluded that E (DB) increases with the degree of confinement and that E (DB) >1.10 eV for the isolated dangling bond in the bulk. After Si H dissociation and for the low-temperature processes, hydrogen is transported in molecular form and a low relaxation of the silicon network is promoted. This is in contrast to the high-temperature process for which the diffusion of H in atomic form induces a substantial lattice relaxation that, for the conventional amorphous sample, releases energy of around 600 meV per H atom. It is argued that the density of sites in the Si network for H trapping diminishes during atomic diffusion.
Keywords: Amorphous Silicon; Dangling Bonds; Solar Cells